Emotional Creativity and Its Relationship to Decision-Making Quality among University Students - عبد الحافظ, ثناء عبد الودود (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The present study aims to achieve the following objectives: 1. To measure emotional creativity among university students. 2. To identify differences in emotional creativity among university students according to the variables of gender (male–female) and academic specialization (scientific–humanities). 3. To measure the quality of decision-making among university students. 4. To identify differences in decision-making quality among university students according to the variables of gender (male–female) and academic specialization (scientific–humanities). 5. To examine the nature of the relationship between emotional creativity and decision-making quality among university students. 6. To identify differences in the nature of the relationship between emotional creativity and decision-making quality according to the variables of gender (male–female) and specialization (humanities–scientific). The study population was defined as university students from the first to the fourth academic year at Baghdad universities during the 2024–2025 academic year. To achieve the research objectives, the researcher relied on the following procedures: 1. Developing a scale to measure emotional creativity among university students based on relevant literature and theoretical frameworks. In its final form, after establishing validity, reliability, and discriminative power, the scale consisted of 32 items distributed across four domains: flexibility, originality, novelty, and effectiveness. 2. Developing a scale to measure decision-making quality, which consisted of 20 items. Statistical analysis of the scale items indicated that they possessed statistically significant discriminative power at the 0.05 level. The psychometric properties (validity and reliability) of both scales were established. To accomplish these objectives, the two scales were administered to a sample of 200 male and female students at the University of Baghdad during the 2024–2025 academic year. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) and Microsoft Excel. The results indicated that university students across both scientific and humanities disciplines possess a high level of emotional creativity. Statistically significant differences in emotional creativity were found according to gender and specialization, in favor of males and students in the humanities. In addition, students in both scientific and humanities fields demonstrated a good level of decision-making ability. Based on these findings, the study concluded with a number of practical recommendations and proposals.